Anticancer Gold N‐Heterocyclic Carbene Complexes: A Comparative in vitro and ex vivo Study. (29th August 2017) - Estrada‐Ortiz, Natalia; Guarra, Federica; de Graaf, Inge A. M.; Marchetti, Lorella; de Jager, Marina H.; Groothuis, Geny M. M.; Gabbiani, Chiara; Casini, Angela
Abstract: A series of organometallic Au I N ‐heterocyclic carbene (NHC) complexes was synthesized and characterized for anticancer activity in four human cancer cell lines. The compounds' toxicity in healthy tissue was determined using precision‐cut kidney slices (PCKS) as a tool to determine the potential selectivity of the gold complexes ex vivo. All evaluated compounds presented cytotoxic activity toward the cancer cells in the nano‐ or low micromolar range. The mixed Au I NHC complex, ( tert ‐butylethynyl)‐1, 3‐bis‐(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene gold(I), bearing an alkynyl moiety as ancillary ligand, showed high cytotoxicity in cancer cells in vitro, while being barely toxic in healthy rat kidney tissues. The obtained results open new perspectives toward the design of mixed NHC–alkynyl gold complexes for cancer therapy. Abstract : The Midas touch : A novel series of gold(I) N ‐heterocyclic carbene (NHC) complexes were prepared and characterized. The antiproliferative activities of the compounds were tested in four human cancer cell lines, and their toxicity in healthy tissue was determined using rat precision‐cut kidney slices (PCKS) showing interesting activities in both in vitro and ex vivo models.